Tuvan armed rebellion in 1930 - Samdan, Ayana A. (The New Research of Tuva, 2020)
The article presents a reconstruction of an armed rebellion in 1930 in Tuvan People’s Republic based on previously unpublished archival documents, including regulations issued by legislative and executive authorities, party offices and participants’ memoirs.One of the reasons for the rebellion was a change in the domestic policy of the TPR, starting from the 8th Congress of Tuvan People’s Revolutionary Party (Autumn 1929). It granted the leading role in running the country to the party, proclaimed adherence to a non-capitalist way of development, and removed former feudal lords and officials from any role in the state and public administration of the country. These transformations were felt by a broad circle of public, including former noyons, officials and lamas, who were mostly deprived of their political and civil rights. This led to the protest movement on a broad scale. The Tuvan revolt was not unique: a similar process was happening at the same time in Mongolia (culminating in the 1930-1932 rebellion), so the slogans in both countries were quite similar. The rebels rose against the government actions, supported a restoration of the former political authority and the Buddhist religion, but they failed to develop a specific program.The riots in TPR broke out in March 1930 in the Western regions of Tuva, including Dzun-Khemchiksky, Ovyursky, Barun-Khemchiksky, Mongun-Tayginsky, Tandinsky, Piy-Khemsky and Ulug-Khemsky kozhuuns (districts). The total number of rebels is difficult to specify, but it can be approximated as c. 400 people. According to the documents, they were led by former officials and the wealthy, but the rebels themselves mostly came from the poor.The main reason for the rebels’ defeat was their inability to unite. Pockets of rebellion were periodically recorded in some areas of Tuva in 1931, 1932, and 1933.
Keywords: Tuva; armed rebellion; Tuvan history; Mongolian history; Tuvan People’s Republic; Tuvans; Panchen-lama IX